Development of a usable online counseling management system - Wan Norizan, Wan Hashim; Mohd Razali, Othman; Safi’ee, Madian; Mohamad Izzat, Syafiq (Elsevier Ltd, 2013)
This paper is aimed at identifying solution regarding counseling management of employees’ life problem including personal and work place problems. This paper involved the design, development and evaluation of Employee Needs Assessment Inventory (ENAI) functionality and usability among employees in Malaysia. This project used a quantitative approach called case study in the process of collecting data. In general, this project was divided into three phases: system requirements analysis, system design and development, and formative evaluation. The result from of ENAI formative evaluation had proven that the system could be able to record employees’ life problem (health, family, financial, spiritual, work issue, career, interpersonal relationship and work environment). Besides, the system can be used by three tiers (employees, employer and counselor) to access the counseling information, provide communication networking facility for a diversity user, and assist in the generation of reports and analysis, and also to support counseling management for the three tiers.